Konsep Pendidik Perspektif Az-Zarnuji - Moh. Faizin; Muhammad Fikri Haikal Pratama; Reza Nabila (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze and describe the effectiveness and contribution of the This article discusses in depth the concept of educators according to Az-Zarnuji's perspective in his book "Ta'lim al-Muta'allim" (Education for Learners), which is one of the important works in the field of classical Islamic education. Al-Zarnuji does not view educators solely as conveyors of knowledge (teachers), but also as moral guides (educators) and character builders (educators). This study stems from the phenomenon of moral decline, a crisis of role models, and a decline in the integrity of educators, which contradicts the values of Islamic education. Using a descriptive-qualitative approach, the discussion focuses on Az-Zarnuji's biography, his views on the nature, duties, and responsibilities of teachers, as well as the criteria for ideal teachers, which include knowledge, piety, honesty, fairness, and moral maturity. Al-Zarnuji also emphasizes the importance of the mystical and practical dimensions in education, namely the development of students' spirituality and the teaching of knowledge in a systematic, contextual, and useful manner for life. According to Az-Zarnuji, the ideal educator is a figure who combines intellectual intelligence, moral exemplarity, and spiritual sincerity, so as to be able to produce a generation that is educated, civilized, and has a strong character. This concept is still relevant as a philosophical and ethical basis for shaping the personality, professionalism, and moral integrity of teachers in a complex and spiritually difficult modern era, where teachers are expected to be able to deal with social and technological dynamics without forgetting the roots of pure Islamic values.